PENGARUH RETURN ON ASSETS (ROA), EARNING PERSHARE ( EPS), DIVIDEND PAYOUT RATIO DAN LEVERAGE TERHADAP HARGA SAHAM (STUDI KASUS PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI 2007-2010) - Dwi Widiyanti, 08.05.51.0148; Sudarsi, Sri (Students Journal of Economic and Management, 2013)
This purpose of this study to examine and analyze the effect of Return on Assets (ROA), Earning Pershare (EPS), Divident Payout Ratio (DPR) and Leverage ratio of the Price stock. Objects in this study is a company registered in the BEI (Bursa Efek Indonesia) Jakarta during 4 years period from 2007 until 2010. The samples in this study were 111 samples. The method used in the sampling is purposive sampling method. Statistic alanalysis tool used is regression. The results show that Return on asset, Earning Pershare and divident payout Ratio were significant influence to price stock. Leverage no significant effect on stock price.Key words: Return on asset, Earnings pershare, Dividend payout ratio, Leverage and Price stock .